A Prospective Study and Analysis of the Pattern of Antimicrobial Utilization for Urinary Tract Infection in Tertiary Care Hospital: Pharmaceutical Science-Pharmacy Practice - Abdolmalaki, Parastoo; Koneri, Raju (International Journal of Life Science and Pharma Research, 2022)
Monitoring utilization pattern of antimicrobial drugs for the treatment of UTIs can provide an important vision into a rational prescription of antimicrobials and prevent inappropriate therapeutic outcomes. This study aimed to focus on the study and analysis pattern of antimicrobial utilization in the management of UTI among patients admitted to a tertiary care hospital. A prospective study was conducted over six months in the Medicine Department of Bangalore Baptist Hospital, Bangalore, India. A total of 150 patients with UTI aged ≥ 18 years were included in the study, of which the majority of patients were female. A comorbidity analysis showed that forty-one (27.3%) patients had diabetes mellitus followed by hypertension (39, 26%), renal failure (23, 15.4%), renal calculi (17, 11.3%), and malaria (8, 5.3%). E. coli (23, 54.76%) was the most common isolated organism. Analysis of the utilization pattern of antimicrobial drug classes in patients with urinary tract infection revealed that cephalosporin (90, 60%) was the most-common prescribed class of antimicrobial drugs for management of UTI. Cefotaxime (47, 31.33%) was the most commonly prescribed cephalosporins. Fluoroquinolones (42, 28%) were the second most common pharmacologic class of antimicrobial drugs prescribed for the treatment of UTI of which ciprofloxacin (18, 12%) was the most commonly used fluoroquinolone. Overall, we identified 41 (Drug-Drug Interactions) DDIs between prescribed antimicrobial drugs and other medications. Interaction between ceftriaxone and calcium salts (13, 31.71%) was found to be the most commonly identified DDI. A periodic review of antimicrobial utilization patterns should be performed to enhance the empirical treatment of UTIs according to patients` urine culture reports. Our study findings provide feedback to prescribers to stimulate thinking about their practice and look for ways to improve rational antimicrobials prescription, and patient safety.